2013
DOI: 10.1002/mnfr.201200529
|View full text |Cite
|
Sign up to set email alerts
|

3‐Caffeoyl, 4‐dihydrocaffeoylquinic acid from Salicornia herbacea attenuates high glucose‐induced hepatic lipogenesis in human HepG2 cells through activation of the liver kinase B1 and silent information regulator T1/AMPK‐dependent pathway

Abstract: These results indicate that CDCQ prevented lipid accumulation by blocking the expression of SREBP-1c and FAS through LKB1/SIRT1 and AMPK activation in HepG2 cells, suggesting that CDCQ plays a potential role in the prevention of lipogenesis by AMPK activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 47 publications
3
22
1
Order By: Relevance
“…Chiang et al reported that augmentation of AMPK cascade and subsequent inhibition of FAS expression caused by exposition of colon cancer CRC cells to CA derivatives inhibited the growth of cells [14]. The results presented by Hwang et al indicated that Chlorogenic Acid derivatives isolated from Salicornia herbacea may exert cytotoxic effect on and decrease proliferation of human Hep G2 cells, including AMPK activation and resulting impaired expression of SREBP-1c and FAS proteins [29]. A similar mechanism was reported in Hep G2 cells for other polyphenolic compound, Epigallocatechin Gallate (EGCG) [30].…”
Section: Discussionmentioning
confidence: 99%
“…Chiang et al reported that augmentation of AMPK cascade and subsequent inhibition of FAS expression caused by exposition of colon cancer CRC cells to CA derivatives inhibited the growth of cells [14]. The results presented by Hwang et al indicated that Chlorogenic Acid derivatives isolated from Salicornia herbacea may exert cytotoxic effect on and decrease proliferation of human Hep G2 cells, including AMPK activation and resulting impaired expression of SREBP-1c and FAS proteins [29]. A similar mechanism was reported in Hep G2 cells for other polyphenolic compound, Epigallocatechin Gallate (EGCG) [30].…”
Section: Discussionmentioning
confidence: 99%
“…The tumor suppressor LKB1, a protein ubiquitously expressed by mammalian cells, has been demonstrated to activate AMPK [35], [43][47]. It has been reported that LKB1 is activated by two putative kinases; i.e., STE20-related adaptor protein (STRAD) and mouse protein 25 (MO25) [48].…”
Section: Discussionmentioning
confidence: 99%
“…Previous phytochemical studies on the genus Salicornia described the isolation of a variety of compounds: benzopyrones, lignans, flavonoids, saponins, coumarins, terpenoids, quinic acid derivatives and alkaloids [26][27][28][29][30][31][32][33][34][35][36][37][38]. To the best of our knowledge, no phytochemical work have been conducted on S. gaudichaudiana.…”
Section: Introductionmentioning
confidence: 96%
“…[26,32,38]. These compounds showed typical mass cleavages of m/z 162 and m/z 164, indicating the neutral loss of one caffeic acid and a dihydro-caffeic acid unit, resulting in characteristic MS/MS fragment ions at m/z 355 and 353.…”
mentioning
confidence: 95%